Analysis Determinants of GRDP in East Java: Aprroach Investment and Employment - Fahri Ardiansyah Andhi Hisyam; Muhammad Arif (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
This study aims to analyze the influence of investment, employment, human development, unemployment, poverty, and minimum wages on Gross Regional Domestic Product (GRDP) of districts/cities in East Java using a panel data regression approach with the best Fixed Effect Model (FEM) based on the Hausman test. The results show that the Human Development Index (HDI) and district minimum wages (Wage) have a positive and significant effect on GRDP, which means that improving the quality of education, health, and living standards as well as increasing community income can increase productivity and consumption, thereby encouraging regional economic growth. Conversely, the open unemployment rate (Unemp) and the number of poor people (Pov) have a negative and significant effect, which indicates that high unemployment reduces people's income and purchasing power, while poverty suppresses aggregate demand and economic participation, thus hampering growth. Meanwhile, foreign direct investment (FDI) and the labor force participation rate (Lab) do not have a significant effect on GRDP, which indicates that uneven foreign investment and low quality and absorption of labor cause these two variables to be unable to provide a real contribution to economic output. This research contributes to filling the gap in previous research by integrating various economic variables in a comprehensive model based on panel data in 38 districts/cities in East Java, so that it can provide a more comprehensive picture of the determinants of GRDP and become the basis for formulating more targeted regional economic development policies.